Mesothelial Cyst of the Round Ligament Misdiagnosed as Irreducible Inguinal Hernia. (18th September 2013) - Manatakis, Dimitrios K.; Stamos, Nikolaos; Agalianos, Christos; Vamvakas, Panagiotis; Kordelas, Athanasios; Davides, Demetrios
Abstract : We report the case of a 36-year-old woman who presented with signs and symptoms of an irreducible inguinal hernia. Surgical exploration revealed a mesothelial cyst of the round ligament of the uterus. Mesothelial cysts of the round ligament are rare lesions, frequently masquerading as inguinal hernias, and should be included in the differential diagnosis of any inguinal mass. Clinical findings are those of a groin mass, discomfort, and bulging. Ultrasound and CT scans often demonstrate an aperistaltic cystic mass. Definitive diagnosis is usually made intraoperatively and confirmed histopathologically.